Kajian Terhadap Debit Dan Kualitas Air Sumur Bor Di Kelurahan Jabungan - Sugiharto, Suparman (Jurusan Teknik Sipil, Politeknik Negeri Semarang), A. Sutowo Latief (Jurusan Te (Teknis, 2015)
This study specifically aims to: (1) determine the water discharge drill wells, (2) analyzing the physical, chemical and microbiological before and after filtered. Water discharge is determined by the volume of water coming out of the pump, housed in a bucket or vessel in time-varying, repetition is done ten (10) times. Water discharge is determined from the average price of the volume of water being stored in the bucket divided time it takes to fill it. Based on a simple statistical calculation, the discharge of water after filtration is 1.31 l / s, before filtrationÂ  Â of 1.86 l / s, so that the filtration efficiency of 70.4%. Analysis of the composition of the water carried by physical, chemical and microbiological conducted in the laboratory total solids showed 460 ppm and 330 ppm prior to filtration, after filtration, the quality standard of 1,500 ppm. Chemical properties of the water before and after filtration, namely: pH 7, the quality standard (6.5 to 9.2). Total hardness initially 223.32 ppm to 181.56 ppm, while the quality standard of 500 ppm CaCO3. Nitrite has decreased from 0.38 ppm to < 0.02 ppm, but not yet eligible to be negative. Sulfate, lead and copper negative, chloride remained 16.588 ppm, well below the quality standard of 600 ppm. Although iron decreased from 218.72 before filtration into 184.8 ppm after filtration, but the maximum quality standard of 1 ppm Fe, thus not eligible drinking water.Keywords: assessment, discharge, water quality, wellbore